Existence and multiplications of solutions for a class of equation with a non-smooth potential - Fariba Fattahi; M. Alimohammady (Journal of Hyperstructures)
This paper deals with the existence and multiplicity of solutions for a class of nonlocal p−Kirchhoff problem. Using the mountain pass theorem and fountain theorem, we establish the existence of at least one solution and infinitely many solutions for a class of locally Lipschitz functional.